Assimilation in American Life: An Islamic Perspective (American Journal of Islam and Society, 1991)
AbstractThe influx of Muslim immigrants into America has become steady inthe last decade, a development which raises the need for a theoretical outlookdelineating a model of an Islamic-controlled process of assimilation.Using Gordon’s model of assimilation, the paper suggests an Islamicposition regarding each of his seven types and stages of assimilation.In respect to cultural assimilation, the paper advocates an interactiveprocess of assimilation on the level of extrinsic cultural traits. Such a processutilizes six filtration procedures regarding different kinds of American culturalartifacts. But on the level of intrinsic cultural traits, the paper suggests acounterassimilation position, and considers it a cornerstone in keeping theoriginality of Islam.As to identificational assimilation, the paper defines Islamic boundariesrelevant to each of its three components: ethnic, national, and racial.The paper discusses behavior-receptional and attitude-receptional typesof assimilation in light of patterns of behavior that affect such reciprocity.The paper argues that civic assimilation is a crucial area where much ofthe Muslim community’s efforts could be invested.Finally, the paper briefly discusses marital assimilation and structuralassimilation.IntroductionAssimilation is an important subject that deserves careful considerationfrom minorities, marginal groups, and immigrants. The position of a groupon assimilation has far-reaching effects on its present and future, as well ...